Internal factors affecting Islamic banks profitability in Malaysia / Muhammad Syazwan Mohd Zulbahrin - Mohd Zulbahrin, Muhammad Syazwan (Faculty of Business Management, 2018)
This paper is aims to investigate the internal factors that affect Islamic Banks' profitability in Malaysia. This study shall focus on seven local Islamic commercial banks in Malaysia taken from the list of Islamic banks provided by Bank Negara Malaysia. The internal factors taken into consideration of which may affect banks' profitability shall be observed closely. The dependent variable in this study is Islamic banks' profitability, measured by Return on Assets (ROA). Four selected independent variables in this study are size of banks (SIZE), capital adequacy ratio (CA) and financing/loan ratio (FIN) anci deposit ratio (DEP). The data from the sample of nine Islamic banks are pooled for six years (2011-2016). The data used in this research is quantitative secondary data and is a panel data structure. In addition, the research was conducted using panel least squares method to generate result for this study. Previous studies have had mixed results though samples were different. This research however, has found that CA has a significant negative relationship with ROA while DEP, FIN, and SIZE all have an insignificant positive relationship return on assets. The result obtained for CA indicates that, an increase in CA would cause a decrease in ROA.